2010
DOI: 10.1007/s13191-010-0009-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of crown and bridge work quality among Sudanese dental practitioners

Abstract: It is concluded that the majority of the surveyed dentists mainly used alginate as a final impression material for crown and bridge work. It was also observed, the absence of application of retraction cord and temporary restoration in their practice for crown and bridge work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 9 publications
0
19
1
Order By: Relevance
“…Wax was the most popular registration material, being selected by 100 DP's (94.3%), followed by silicone 5 (4.7%) and silicone putty 1 (0.9%). [9] In present study the majority of respondents, 242 (83.4%) always took bite registration for multiple teeth replacement and wax was the most used material for bite registration 179 (61.7%). Prevention of cross infection in dental practice in general and dental laboratory specifically should now be a routine in practice.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Wax was the most popular registration material, being selected by 100 DP's (94.3%), followed by silicone 5 (4.7%) and silicone putty 1 (0.9%). [9] In present study the majority of respondents, 242 (83.4%) always took bite registration for multiple teeth replacement and wax was the most used material for bite registration 179 (61.7%). Prevention of cross infection in dental practice in general and dental laboratory specifically should now be a routine in practice.…”
Section: Discussionmentioning
confidence: 61%
“…[8] Amruta et al found that, 51% do not practice gingival retraction, 46% of practitioners use gingival retraction cord, 2% do rotary curettage, 1% use laser and electro-surgery seems rarely used for gingival retraction by private dental practitioners. [10] In the other hand, Only 9.4% used retraction cord while 53.7% of the surveyed DP's never adopted the use of retraction cords,[9] while in the current study 117 (40.3%) of respondents always use retraction cord and 15 (5.2%) never use retraction cord. Regarding using of inter-occlusal record.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations